2009
DOI: 10.1002/jssc.200900204
|View full text |Cite
|
Sign up to set email alerts
|

In situ ethylation of organolead, organotin and organomercury species by bromomagnesium tetraethylborate prior to GC‐ICP‐MS analysis

Abstract: An analytical method for simultaneous in situ ethylation, of organolead, organotin and organomercury compounds in aqueous samples was developed using a new derivatisation agent, bromomagnesium tetraethylborate (BrMgEt(4)B). The determination of lead, tin and mercury compounds was done by species-specific isotope dilution, derivatisation and GC-inductively coupled plasma MS (GC-ICP-MS) or by GC-MS. The recovery and accuracy of the derivatisation were evaluated. The effect of pH and the relative quantity of deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Alternatively, chloroformate [60] and cyanogen bromide [61] have been used as devertization reagents for the determination of seleno amino acids. Moreover, synthesized BrMgEt 4 B was used for in situ ethylation of organolead, organotin and organomercury to replace the commercially available high cost alkylborates [62]. Recently, Yan et al [63] reported to use butyl magnesium bromide as a derivatization reagent to avoid the loss of species specific information of analytes and employed synthesized Pr 3 PbCl as an alternative internal standard to improve the analytical precision and accuracy for the simultaneous determination of different Pb and Hg species.…”
Section: Alkylationmentioning
confidence: 99%
“…Alternatively, chloroformate [60] and cyanogen bromide [61] have been used as devertization reagents for the determination of seleno amino acids. Moreover, synthesized BrMgEt 4 B was used for in situ ethylation of organolead, organotin and organomercury to replace the commercially available high cost alkylborates [62]. Recently, Yan et al [63] reported to use butyl magnesium bromide as a derivatization reagent to avoid the loss of species specific information of analytes and employed synthesized Pr 3 PbCl as an alternative internal standard to improve the analytical precision and accuracy for the simultaneous determination of different Pb and Hg species.…”
Section: Alkylationmentioning
confidence: 99%
“…Most of the analytical methodologies for determination of TBT are based on gas chromatography (GC) owing to its high resolution and the compatibility with highly sensitive detectors like mass spectrometric (MS), flame photometric (FPD) and microwave induced plasma atomic emission detectors (MIP‐AED) (Birjandi et al ., ; Chou and Lee, ; Tutschku et al ., ; Zachariadis and Rosenberg, ). More recently many workers studied the benefits of hyphenated techniques such as liquid and gas chromatography attached to ICP‐MS (González‐Toledo et al ., ; Nsengimana et al ., ; Point et al ., ; Vahcic et al ., ; Xiao et al ., ) for the speciation analysis of organotins in environmental and biological samples. The accuracy of organotin determination in environmental or biological samples depends not only on the measurement step but also on the sample preparation, sampling and storage conditions, which potentially affect the reliability of the results (Abalos et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Another advantage of the present technique was detection method. HPLC offers the advantage that the derivatization procedure is not required, which was chosen in this work instead of GC in the reported methods . HPLC has good separation efficiency, fast operation, and many available detectors, such as atomic absorption spectroscopy (AAS) , inductively coupled plasma atomic emission spectroscopy (ICP‐AES) , MS , UV spectrophotometry (UV) , and inductively coupled plasma mass spectrometry (ICP‐MS) .…”
Section: Introductionmentioning
confidence: 99%